Analyzing the drivers of smallholder farmer’s market participation in the Sahelian region of Niger - Zakari, S.; Moussa, B.; Ibro, G.; Abdoulaye, T. (Informa UK Limited, 2023)
Many sub-Saharan farmers rely on agricultural production for home consumption and sell crops to meet their other needs. Farmers’ market intervention enhances economic expansion and helps to improve household food security. In our current study, we strive to explore the determinants of farmers’ decisions and the intensity of market participation in the Sahelian region of Niger, where little has been published, thereby filling the gap in the literature. A double hurdle approach was employed to achieve this objective using a sample collected from 1784 farm households in Niger.